Analysis of the study of long songs of Upper Mongolia (Mongolian Journal of Arts and Culture, 2024)
This article is written for the purpose of analyzing the researched status of Upper Mongolian long songs. In 2018, I, the author, obtained a master’s degree at the Mongolian University of Culture and Arts on the subject of “Musical techniques of long longs of Upper Mongolian long song with horse fiddled music”. Since then, in the process of in-depth study of the long songs of Upper Mongolia, I have conducted field research in 2017, 2019, 2020, and 2023 in Khukh Lake, the birthplace of long songs, and have reviewed and collected books and articles related to long songs in that area and in Beijing and Hoh as well as classified and summarized them.I accordance with the research, studies have been conducted on the historical significance of long songs of Upper Mongolia, their types, singing rituals, poems, and versions of melodies, inheritance, and preservation.As well as, in the future, there is still a need to study the long songs of Upper Mongolia in the context of their roots, structure, artistic features and unique characters.Дээд монголын уртын дууны судлагдсан байдалд хийсэн шинжлэлХураангуй: Энэхүү өгүүллийг Дээд монголын уртын дууны судлагдсан байдалд дүн шинжилгээ хийх зорилгоор бичиж байна. Зохиогч миний бие 2018 онд Монгол Улсын Соёл урлагийн их сургуульд “Дээд монголын уртын дууг хуурдах арга барил” сэдвээр магистрын зэрэг хамгаалсан ба түүнээс хойш Дээд монголын уртын дууг гүнзгийрүүлэн судлах явцдаа уртын дууны өлгий нутаг болох Хөх нуурт 2017, 2019, 2020, 2023 онуудад хээрийн судалгаа хийж, тухайн орон нутагт болон Бээжин, Хөх хотод хэвлэгдсэн холбоотой ном бүтээл, өгүүлэлтэй танилцан, цуглуулж, уг бүтээлүүдэд ангилал хийн, нэгтгэн дүгнэсэн. Судлагдсан байдлаас үзэхэд, Дээд монголын уртын дууны түүхэн холбогдол, төрөл зүйл, дуулах зан үйл, шүлэг, аялгууны хувилбар, өвлөн уламжлах, хадгалан хамгаалах талаар судалгаанууд түлхүү хийгдсэн байна. Цаашид Дээд монгол уртын дууг язгуур шинж, бүтэц, уран сайхны онцлог гэх өргөн агуулгын хүрээнд судлах шаардлага байсаар байна.Түлхүүр үгс: Дээд монгол, урт дуу, судлагдахуун, шинжлэл